SERS-Active Gold Lace Nanoshells with Built-in Hotspots - Yang, Ming (2010)
Development of multifunctional drug delivery vehicles with therapeutic and imaging capabilities as well as in-situ methods of monitoring of intracellular processes will greatly benefit from a simple method of preparation of plasmonic Au structures with nanometer scale gaps between sharp metallic elements where the so called SERS hot spots can be formed. Here the synthesis of gold lace capsules with average diameters ca. 100 nm made of a network of metallic branches 3–5 nm wide and separated by 1–3 nm gaps is reported. Biocompatible amphiphilic polyurethanes (PUs) were used as template for these particles. The unusual topology of the produced gold lace shells somewhat reminiscent of Fabergé eggs is likely to reflect the network of hydrophobic and hydrophilic domains of PU globules. The gold lace develops from initial open web-like structures by gradual enveloping the PU template. The diameter of gold lace shell is determined by the size of PUs in water and can be adjusted by the molecular mass of PUs. The close proximity between branches makes them excellent supports for surface enhanced Raman spectroscopy (SERS) which was demonstrated using 1-naphthalenethiol upon excitation with photons with different wavelengths. The loading and releasing of pyrene as a model of hydrophobic drugs and the use of SERS to monitor it were demonstrated.